Can Pallars i Llobateres: A new hominoid-bearing locality from the late Miocene of the Vallès-Penedès Basin (NE Iberian Peninsula). Issue 121 (August 2018) - Alba, David M.; Casanovas-Vilar, Isaac; Furió, Marc; García-Paredes, Israel; Angelone, Chiara; Jovells-Vaqué, Sílvia; Luján, Àngel H.; Almécija, Sergio; Moyà-Solà, Salvador
Abstract: In the Iberian Peninsula, Miocene apes (Hominoidea) are generally rare and mostly restricted to the Vallès-Penedès Basin. Here we report a new hominoid maxillary fragment with M 2 from this basin. It was surface-collected in March 2017 from the site of Can Pallars i Llobateres (CPL, Sant Quirze del Vallès), where fossil apes had not been previously recorded. The locality of provenance (CPL-M), which has delivered no further fossil remains, is located very close (ca. 50 m) to previously known CPL outcrops, and not very far (ca. 500 m in NW direction) from the classical hominoid-bearing locality of Can Poncic 1. Here we describe the new fossil and, based on the size and proportions of the M 2, justify its taxonomic attribution to Hispanopithecus cf. laietanus, a species previously recorded from several Vallesian sites of the Vallès-Penedès Basin. Based on the associated mammalian fauna from CPL, we also provide a biochronological dating and a paleoenvironmental reconstruction for the site. The associated fauna enables an unambiguous correlation to the Cricetulodon hartenbergeri – Progonomys hispanicus interval local subzone, with an estimated age of 9.98–9.73 Ma (late Vallesian, MN10). Therefore, CPL-M is roughly coeval with the Hispanopithecus laietanus -bearing localities of Can Llobateres 1 and Can Feu 1, and minimally older than those of La Tarumba 1 and Can Llobateres 2. In contrast, CPL-M is younger than the early Vallesian (MN9) localities of Can Poncic 1 (the type locality of Hispanopithecus crusafonti ) as well as Polinyà 2 (Gabarró) and Estació Depuradora d'Aigües Residuals–Riu Ripoll 13, where Hispanopithecus sp. is recorded. The associated fauna from CPL indicates a densely forested and humid paleoenvironment with nearby freshwater. This supports the view that Hispanopithecus might have been restricted to dense wetland forests soon before its extinction during the late Vallesian, due to progressive climatic deterioration. Coupled with the existence of other fossiliferous outcrops in the area, this find is most promising for the prospect of discovering additional fossil hominoid remains in the future.